SREBP-1a Polymorphism Influences the Risk of Alzheimer’s Disease in Carriers of the ApoE4 Allele - Spell, Christian; Kölsch, Heike; Lütjohann, Dieter; Kerksiek, Anja; Hentschel, Frank; Damian, Marinella; Bergmann, Klaus von; Rao, Marie Luise; Maier, Wolfgang; Heun, Reinhard (Dementia and geriatric cognitive disorders, 2004)
Sterol regulatory element-binding proteins (SREBPs) are transcription factors involved in cholesterol and fatty acid synthesis. Recently, a polymorphism in the 5′-region of the SREBP-1a gene has been described to be correlated with alterations in the plasma levels of cholesterol. Consequently the relationship between this SREBP-1a gene polymorphism and Alzheimer’s disease (AD) alone and in combination with the apolipoprotein E (ApoE) 4 allele was evaluated. No association between SREBP-1a polymorphism alone and AD could be seen. However, in the group of healthy ApoE4 allele carriers, the number of homozygote SREBP-1a ΔG allele carriers was significantly higher than in AD patients. Cerebrospinal fluid levels of cholesterol were lower in AD patients who were carriers of the SREBP-1a ΔG allele, and the ratio of 24S-hydroxycholesterol to cholesterol was increased in these probands. Our data suggest a reduced risk of AD in carriers of an ApoE4 allele who are additionally homozygous for the SREBP-1a ΔG allele, which is possibly due to the influence of SREBP-1a polymorphism on brain cholesterol metabolism. This is the first report on a genetic factor which prevents the deleterious effect of the ApoE4 allele and thus reduces the risk of AD.
Gesehen am 11.11.2020